Personality traits, risk aversion and endowment effects on residential mobility outcomes. (March 2023) - Clark, William A.V.; Ong ViforJ, Rachel; Phelps, Christopher
Abstract: The psychology literature offers substantial evidence suggesting that personality traits are associated with different residential mobility patterns. Our study extends this previous work by examining whether the effects of personality traits on mobility are attenuated by risk aversion and endowment effects. We also investigate whether personality traits exert an indirect influence on mobility through risk aversion and endowment effects. We draw on data from the Household, Income and Labour Dynamics in Australia Survey over the period 2014–2018. We find that openness and extraversion have positive associations with residential mobility, but risk aversion and endowment effects reduce the likelihood of moving. Moreover, risk aversion and endowment effects act as mediators through which openness and extraversion exert an indirect influence on residential mobility. These mediators account for 35 % and 30 % of the total effect on mobility exerted by openness and extraversion respectively. The types of individual differences that matter for residential mobility also vary by sex and age, reflecting the influence of life course contexts on residential mobility outcomes. Highlights: Openness and extraversion have positive associations with residential mobility. Risk aversion and endowment effects are negatively associated with mobility. Personality influences mobility indirectly through risk aversion and endowment. Individual differences that matter for residential mobility vary by sex and age.